Hamilton, Mo., Rev. Ordinances ch. 21, § 162 (1903) - (:unkn) unknown (My University, 1903)
Laws concerning carrying weapons in certain places, sales of weapons to minors, etc., Chapter 21-Misdemeanors, § 162: Any person who shall carry concealed upon or about his person any deadly or dangerous weap§on, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people are assembled for educa§tional, literary or social purposes, or to any election pre§cinct on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose, other than for malitia [sic] drill, having upon or about his person any kind of fire arms, bowie knife, dirk, dagger, sling shot or oth§er deadly weapon, or shall, in the presence of one or more persons, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks, or shall, di§rectly or indirectly, sell or deliver, loan or barter, to any minor any such weapon without the consent of the par§ent or guardian of such minor, he shall be deemed guilty of a misdemeanor
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS